THE EFFECT OF FAMILY OWNERSHIP ON PROFIT AND PERFORMANCE COMPANY MANAGEMENT: BASED ON THE THEORY OF STEWARDSHIP - Andayani, Wuryan; Hartono, Jogiyanto; Supriyadi, Supriyadi; Miharjo, Setiyono (Universitas Brawijaya, Indonesia, 2018)
This study examines the relationship between family ownership of a company and its implications for earnings quality. In the family ownership, the family can affect the quality of earnings that are reported in two ways, namely through the entrenchment and the alignment effect. Earnings are managed opportunistically shows a low earnings quality. Whereas the influence of alignment shows a high quality where earnings are not managed opportunistically. The study also examines if the family ownership has a positive effect on company performance. There are five factors that affect innate accruals quality, namely the company size, the standard deviation of operating cash flows, the standard deviation of sales, duration of operating cycles, and negative earnings. Quality of accruals consists of accruals that reflect economic conditions and accruals that reflect managerial choices. This study shows that family-owned companies in Indonesia do not perform earnings management opportunistically. Earnings management used is the one that is in line with the company's business model, company industrial environment and economic conditions as represented by innate accruals. This suggests that family ownership has an earnings quality and shows an alignment of interest between the company management and the owners. Thus the alignment of the interests lends support to the stewardship theory.